WHY IS THE STUDY OF THE COMPLEX SAFETY OF CELECOXIB FOR ARTHRITIS, WHICH IS CALLED PRECISION, LAST BUT NOT LEAST? - Yu. V. Muravyev (Научно-практическая ревматология)
The paper discusses the results of the long-term PRECISION study specially designed for the prospective comparative evaluation primarily of the cardiovascular safety of celecoxib, ibuprofen, and naproxen, which are long used for the treatment of pain in patients with arthritis.